Geração distribuída de energia solar fotovoltaica na matriz elétrica de Curitiba e região: um estudo de caso - Campos, Henrique Marin van der Broocke (2015)
This study aims to deepen knowledge in the item electricity generation planning through the use of distributed generation using solar photovoltaic energy, which means that photovoltaic systems are able to operate in parallel with the electricity distribution network. A hypothetical-deductive approach was developed, seeking hypotheses in the form of guiding questions, which will be tested by treatment of the collected data and their analysis and interpretation. The method of procedure is the case study, being applied to the Metropolitan Region of Curitiba. The literature review aims to be the theoretical basis of this research, therefore it mainly consists of a brief statistical and electrical energy inventory of the city of Curitiba in Paraná state. The methodological procedures involve the simulation of different scenarios for distributed PV generators by varying their Penetration Level, so that the effects on actual load curves for the region analyzed were quantified. 12 critical days were selected to the analysis that included the photovoltaic contribution in terms of reducing electrical energy consumption, reducing CO2 emissions and, finally, the capacity of the photovoltaic systems to reduce the maximum demand of the electrical system of the city. It was concluded that the most appropriate PV Penetration Level, in terms of power, regards with 40,80 MWp up to 55,68 MWp, disconsidering exceptions. This result leads to maximum values of Effective Load Carrying Capacity (ELCC), for maximum and typical solar radiation, during the seasons of winter and summer. In result, this proposed interval represents the better peak shaving capability of PV, because of its higher ELCC parameter. Furthermore, in addition to increase more than 50% in the capacity of the electrical system, there is an annual amount of energy generated about 50.8 GWh and 69.4 GWh, which represents 18,501 to 25,251 tons of CO2-eq avoided. For this reason, solar PV energy is an extremely important and feasible strategy to enhance the electricity generation, the capacity of the electrical system and to reduce greenhouse gases emission, especially CO2.